RELATIONSHIP BETWEEN PATIENT'S TRUST TO THE VISIBILITY LEVEL OF THE OUTBOARD CLINIC DURING THE COVID-19 PANDEMIC - Soedargo, Bayu Prasetyo; Octavian, Henry Sumurung (Kesatuan Press, 2022)
Because of the Covid-19 epidemic, human health care and treatment behavior has moved and changed. Hospital outpatient services have made many attempts to retain patient confidence in restricting the spread of Covid-19 in hospitals. This study aims to see how patient trust in the Covid-19 epidemic condition affects outpatient behavior. Some parts of the study include hospital health protocols, hospital measures to control Covid-19 distribution, and the overall state of Covid-19 dissemination in the city where the hospital is located. A non-probability sampling survey method surveyed 104 outpatients at Melania Hospital in Bogor. The study's findings were analyzed using Structural Equation Modeling to determine patient confidence elements. In addition, the questionnaire's results were examined using descriptions and cross-tabulations of respondent biodata and outpatient behavior. In general, all of the variables investigated have a favorable impact on the respondent's level of trust. Furthermore, these characteristics were examined in importance, starting with the highest and ending with the lowest. Based on this analysis, this report makes marketing recommendations for outpatient services connected to the Covid-19 epidemic